2016
DOI: 10.1007/s12020-016-1172-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of cannabinoid receptor 1 in human adipose tissue for lipolysis regulation and insulin resistance

Abstract: We recently showed that the peripheral cannabinoid receptor type 1 (CNR1) gene is upregulated by the synthetic glucocorticoid dexamethasone. CNR1 is highly expressed in the central nervous system and has been a drug target for the treatment of obesity. Here we explore the role of peripheral CNR1 in states of insulin resistance in human adipose tissue. Subcutaneous adipose tissue was obtained from well-controlled type 2 diabetes subjects and controls. Subcutaneous adipose tissue gene expression levels of CNR1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Here, we found a tendency for increased AT mRNA expression of CNR1 in HWL compared with LWL cows at 4 d PP. Overactivation of the eCB/CB1 receptor system has been documented both centrally and peripherally during obesity and IR[ 26 , 49 , 50 ]. In humans, subcutaneous AT CNR1 expression levels were 2-fold higher in type 2 diabetic subjects compared with controls[ 49 ], suggesting a potential role of the peripheral eCB system in promoting AT dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we found a tendency for increased AT mRNA expression of CNR1 in HWL compared with LWL cows at 4 d PP. Overactivation of the eCB/CB1 receptor system has been documented both centrally and peripherally during obesity and IR[ 26 , 49 , 50 ]. In humans, subcutaneous AT CNR1 expression levels were 2-fold higher in type 2 diabetic subjects compared with controls[ 49 ], suggesting a potential role of the peripheral eCB system in promoting AT dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Overactivation of the eCB/CB1 receptor system has been documented both centrally and peripherally during obesity and IR[ 26 , 49 , 50 ]. In humans, subcutaneous AT CNR1 expression levels were 2-fold higher in type 2 diabetic subjects compared with controls[ 49 ], suggesting a potential role of the peripheral eCB system in promoting AT dysfunction and inflammation. Conversely, and as mentioned previously, all the biological actions reported for CB1 receptor activation in AT in vitro minimize lipolysis[ 14 ], which apparently is in contrast with the tendency for increased expression of AT CNR1 in HWL cows, which exhibited increased lipolysis compared with LWL cows, although we did not examine receptor activation—only gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that a decreased lipase expression and an impaired AT lipolysis may contribute to the development and maintenance of obesity (16,19). However, this explanation is rather unlikely, as HSLdeficient animals are resistant to diet-induced obesity (42), and humans with HSL null mutation display an impaired lipolysis and metabolic disturbances; however, their BMI is usually within the range of overweight and not obese (24). 9:2…”
Section: Figurementioning
confidence: 99%
“…Null mutation in HSL gene leads to impaired AT lipolysis, dyslipidemia, hepatic steatosis, insulin resistance and diabetes (23). Decreased AT expression of MGLL, PLIN1, CIDEA and G0S2 in different conditions associated with insulin resistance was observed (5,24,25,26). The differences in human studies may come from different characteristics of the study groups and different clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ To understand the role of FKBP51 to modify glucocorticoid action in adipocytes, we asked whether the loss of FKBP51 alters the transcriptional activity of the glucocorticoid receptor and thereby its action. We addressed this question by measuring the expression levels of several previously reported glucocorticoid target genes in differentiated adipocytes 6,23 . However, we observed that only CNR1 gene expression was differentially expressed following dexamethasone exposure in wild type vs FKBP51 knockout cultures, respectively.…”
Section: Discussionmentioning
confidence: 99%